The effect of an educational curriculum on developing motor and creative abilities to learn some handball skills - Shawkat Ibrahim, Hatem; KaleelQasim, Laith; Saad Ahmed, Omar (International Journal of Psychosocial Rehabilitation, 2020)
The researchers adopted the experimental approach due to its suitability and the nature of the research. The sample consisted of students from Al-Khabour Mixed Elementary School/Diyala Education Directorate for the academic year 2018-2019. The researchers selected the research sample intentionally from the fifth-grade students (120 pupils) of the fifth elementary school. As for the research sample It consisted of pupils of Division (A) and (B) with an average of (40) pupils for each division, and excluding the pupils represented by (C), the research sample reached (60) pupils, and the sample of exploratory experiments that researchers are conducting their work on and the number (20) A pupil, and the equivalence process between the research groups in some of the creative mobility capabilities and the skill of handling and receiving the handball, and the subject teacher applied the educational curriculum with the comprehensive design of the experimental group and using the method used for the control group, and that the only difference in applying the educational curriculum is in applying the educational curriculum in the comprehensive design in The main section of the experimental research group, the educational curriculum, took (12) educational units and (2) educational units per group per week, and the time of the educational unit was (45) accurate, and the special program used in statistical fields and systems was used.(SPSS) To extract research data, the researchers reached the following conclusions:- program prepared by the researchers and using the comprehensive design method in its application to elementary school pupils has a clear impact on developing some creative kinetic capabilities (kinetic fluency, kinetic flexibility, kinetic originality, learning the skill of handling and receiving the handball.)- The presence of statistically significant differences in the pre- and post-tests and the dimensional dimensions of fluency, flexibility, and motor originality and learning the skill of handling and receiving the handball in the experimental research group that used the comprehensive design method.- Its educational and pedagogical goals have been achieved for the program.